HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN DRIBBLING SEPAKBOLA SISWA SMAN 1 BENGKALIS KECAMATAN BENGKALIS - Effendy, Azwin; Saripin, Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Based on the observation that the author did in the field, is the technique the authors see many students of SMAN 1 Bengkalis District of Bengkalis who lack the agility and good dribbling ability, it is seen as a football player SMAN 1 Bengkalis District of Bengkalis to dribble the ball past your opponent on during a match, at which time the player is difficult to pass opponents, one on one, so the ball is easily seized by the opponent, this was due to lack of students mastering the basic techniques to play ball. This type of research is the correlation. The population in this study were students of SMAN 1 Bengkalis District of Bengkalis many as 36 people. Samples were taken with total sampling technique. thus the number of samples is as many as 36 students. Data collection techniques on agility is a zig-zag run test, while the variable dribbling the ball past mendribbing peg in a zig-zag. Data were analyzed by using the formula produc moment. Based on the results of data analysis showed that of the agility test scores obtained quickest 7:09 seconds, then the longest score of 8.73 seconds, the average (mean) 7:55 seconds. Then the scores obtained from the data dribbling fastest 7.2 seconds, then obtained a score of longest 11.8 seconds, the average (mean) of 8.97 seconds. From these data there exists a correlation result of agility and dribbling ability is 0.9797 which uses formulas Prodac moment. Thus the hypothesis of the importance of the value of r arithmetic 0.9797, while r table 0334. So from 0.9797 arithmetic calculations r> r table (N-1) 0334 can be said that there is a significant relationship between agility (x) the ability of dribbling (y) football SMAN 1 Bengkalis District of Bengkalis.Keywords : Agility, Dribbling